2012
DOI: 10.1158/1078-0432.ccr-11-0879
|View full text |Cite
|
Sign up to set email alerts
|

External Validation of Diagnostic Models to Estimate the Risk of Malignancy in Adnexal Masses

Abstract: Purpose: To externally validate and compare the performance of previously published diagnostic models developed to predict malignancy in adnexal masses.Experimental Design: We externally validated the diagnostic performance of 11 models developed by the International Ovarian Tumor Analysis (IOTA) group and 12 other (non-IOTA) models on 997 prospectively collected patients. The non-IOTA models included the original risk of malignancy index (RMI), three modified versions of the RMI, six logistic regression model… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
1
8

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(79 citation statements)
references
References 45 publications
5
65
1
8
Order By: Relevance
“…A third limitation is that most of the patients in the IOTA phase 3 study were scanned by the same experienced examiners as in the centres where the IOTA methods were developed, or by examiners that had already adopted the IOTA examination technique and terminology. This may explain why the results of IOTA phase 3 confirm those of previous IOTA studies that showed excellent test performance of all IOTA strategies (Timmerman et al , 2005, 2007, 2008, 2010a, 2010b; Van Holsbeke et al , 2009, 2012; Ameye et al , 2012; Kaijser et al , 2013; Sayasneh et al , 2013a, 2013b). On the other hand, validation studies of LR1, LR2 and SRs performed outside IOTA studies reported similar results (Hartman et al , 2012; Nunes et al , 2012, 2013; Alcázar et al , 2013), and there is now evidence that the IOTA strategies retain their performance in the hands of sonographers and relatively inexperienced doctors (Hartman et al , 2012; Nunes et al , 2012, 2013; Alcázar et al , 2013; Sayasneh et al , 2013a, 2013b).…”
Section: Discussionsupporting
confidence: 78%
“…A third limitation is that most of the patients in the IOTA phase 3 study were scanned by the same experienced examiners as in the centres where the IOTA methods were developed, or by examiners that had already adopted the IOTA examination technique and terminology. This may explain why the results of IOTA phase 3 confirm those of previous IOTA studies that showed excellent test performance of all IOTA strategies (Timmerman et al , 2005, 2007, 2008, 2010a, 2010b; Van Holsbeke et al , 2009, 2012; Ameye et al , 2012; Kaijser et al , 2013; Sayasneh et al , 2013a, 2013b). On the other hand, validation studies of LR1, LR2 and SRs performed outside IOTA studies reported similar results (Hartman et al , 2012; Nunes et al , 2012, 2013; Alcázar et al , 2013), and there is now evidence that the IOTA strategies retain their performance in the hands of sonographers and relatively inexperienced doctors (Hartman et al , 2012; Nunes et al , 2012, 2013; Alcázar et al , 2013; Sayasneh et al , 2013a, 2013b).…”
Section: Discussionsupporting
confidence: 78%
“…However, the performance of RMI is poor when applied to masses in young women and pathology that is difficult to be characterised with ultrasound; also, the sensitivity of the test is low. In a study by van Holsbeke et al, the RMI missed 73% of BOTs (31/42 cases) [106].…”
Section: Diagnosismentioning
confidence: 93%
“…We used the data from phase 2 of the IOTA study, which have also been used in previous publications. [17][18][19][20] Patients were recruited between November 2005 and October 2007 in 11 oncology referral centres, three referral centres for ultrasonography, and five general hospitals in eight countries (Belgium, Sweden, Italy, UK, Czech Republic, Poland, China and Canada). The centres are listed in Table 1.…”
Section: Design and Settingmentioning
confidence: 99%
“…These models then underwent temporal validation (IOTA phase 1b, n = 507) and external validation (IOTA phase 2, n = 1938) with excellent performance, 16,17 also in comparison with RMI and other models from the literature as evaluated using the area under the receiver operating characteristics curve. 18 On external validation in 12 centres LR2 and RMI had areas under the curve of 0.95 and 0.91, respectively, and the advantage of LR2 over RMI in terms of area under the curve was larger for premenopausal women than for postmenopausal women. 18 The aim of this study is to compare the RCOG protocol with a protocol based on the IOTA logistic regression model LR2 with respect to the classification of adnexal masses as being at low, moderate or high risk of malignancy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation